Combined natural convection-FSI inside a circular enclosure divided by a movable barrier. (July 2021) - Shahrestani, Ahmadreza B.; Alshuraiaan, Bader; Izadi, Mohsen
Abstract: The natural convection of a Newtonian fluid has been numerically studied inside a partitioned circular enclosure at the presence of a flexible (movable) wall. The set of equations are the continuity equations, the momentum in two directions, the energy equation for the fluid, and the energy and elastodynamic equations for the movable plate. Dimensional parameters indicating the problem are the Rayleigh number (10 4 ≤ Ra ≤ 10 7 ), Prandtl number (0.71 ≤ Pr ≤ 200). The results confirm that The degree of distortion (deformation) of the plate is directly dependent on the amount of forces applied by the fluid. For low Rayleigh numbers, the plate distortion as well as the vortex power produced in both halves of the cavity are almost negligible, and heat transfer dominantly occurs through the conduction mechanism. Increasing the Ra number from 10 4 to 10 7 will enhances the the average Nusselt number more than 5 times. Also, Increasing the Pr number from 0.71 to 200 will significantly increase the total stress applied to the plate more than 70 times.